2019
DOI: 10.1186/s41938-019-0175-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic improvement of Bacillus thuringiensis against the cotton bollworm, Earias vitella (Fab.) (Lepidoptera: Noctuidae), to improve the cotton yield in Pakistan

Abstract: In the present study, CryIAc (Crystal protein) gene was cloned under Cry3A promoter, which is known to express vegetatively as a sporulation independent promoter, transformed into acrystalliferous strain of Bacillus thuringiensis. Its potential was evaluated as a strain to be used for formulation development against the spotted cotton bollworm Earias vitella (Fab.) (Lepidoptera: Noctuidae), the major pest of cotton, the important cash crop in Pakistan. The crystal protein produced in a new strain, i.e., Bt1, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Previous research has reported the factors influencing the expression of Bt insecticidal protein and its corresponding mechanism ( Chen et al, 2005 , 2017 ; Wang et al, 2020 ). Some studies have suggested that tannins produced by cotton plants could bind to insecticidal proteins, which changed the structure of insecticidal protein and inactivated it ( Ma et al, 2012 ); others have suggested that the decreased expression of insecticidal proteins was caused by inactivation of insecticidal protein by methylation promoter of Bt gene ( Yunus et al, 2019 ; Patricia et al, 2020 ); it has also been suggested that changes in the ability of protein synthesis and decomposition can alter the expression of insecticidal proteins ( Chen et al, 2004 , 2005 ; Dong and Li, 2007 ). Chen et al (2017) showed that elevated nitrogen metabolism was beneficial for square development and insect resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported the factors influencing the expression of Bt insecticidal protein and its corresponding mechanism ( Chen et al, 2005 , 2017 ; Wang et al, 2020 ). Some studies have suggested that tannins produced by cotton plants could bind to insecticidal proteins, which changed the structure of insecticidal protein and inactivated it ( Ma et al, 2012 ); others have suggested that the decreased expression of insecticidal proteins was caused by inactivation of insecticidal protein by methylation promoter of Bt gene ( Yunus et al, 2019 ; Patricia et al, 2020 ); it has also been suggested that changes in the ability of protein synthesis and decomposition can alter the expression of insecticidal proteins ( Chen et al, 2004 , 2005 ; Dong and Li, 2007 ). Chen et al (2017) showed that elevated nitrogen metabolism was beneficial for square development and insect resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic crop cultivation expressing the insecticidal cry gene derived from B. thuringiensis, the most successful bioinsecticide, is now a common practice worldwide [62]. These transgenic plants include cotton, cauliflower, tomato, corn, chilli, and eggplants, products famous for their resistance against insects [63]. Two toxins, Cry1Ac and Cry2Ab, have been commercialized for the cotton crop with the name of Bollgard II, protecting against lepidopteran pests [64].…”
Section: Genetic Engineering In Bacillus Applied To Plantsmentioning
confidence: 99%